Nutraceutical effects of organic Selenium and vitamin E supplementation on performance, antioxidant protection and egg quality of Japanese quails (Coturnix japonica) - de Moura, Adolpho Marlon Antoniol; Siqueira Gloria, Leonardo; Vasconcelos Melo, Thiago; de Souza Moura, Guilherme (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
This study evaluated the nutraceutical effects of organic Selenium and vitamin E supplementation on performance, egg quality and antioxidant protection of Japanese quails. Forty-two posture cages with six birds each were randomly set in seven treatments. Each treatment consisted of the addition of 200 IU of vitamin E/kg of feed and increasing levels of organic Selenium. Significant differences were found in α-Tocopherol deposition, enzymatic activity of glutathione peroxidase (GSH-Px) and oxidative bioindicator malondialdehyde (MDA) in egg yolk with vitamin E supplementation. We concluded that supplementing 200mg of vitamin E and 0.30 ppm organic Selenium did not affect bird performance, but improved egg quality and shelf life. Highlights: This study evaluated the nutraceutical effects of organic selenium and vitamin E supplementation on egg quality of Japanese quails. Forty-two posture cages with six birds each were randomly set in seven treatments. Each treatment consisted of the addition of 200 IU of vitamin E/kg of feed and increasing levels of organic selenium. Supplementing 200mg of vitamin E and 0.30 ppm organic selenium did not affect bird performance, but improved egg quality and shelf life.